Artificial life and intelligent agents : first International Symposium, ALIA 2014, Bangor, UK, November 5-6, 2014. Revised selected papers /: first International Symposium, ALIA 2014, Bangor, UK, November 5-6, 2014. Revised selected papers. (2015) - Unknown
No abstract available